Reexamining the notion of Alternative Dispute Resolution (ADR) in the context of the right of access to ‘non-jurisdictional’ justice - Betancourt, Julio Cesar (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The notion of “Alternative Dispute Resolution”, commonly known as “ADR”, has received considerable attention in common law literature, and the same can be said about the main ADR categories (negotiation, mediation and arbitration). ADR, lato sensu, refers to the idea of utilising a wide variety of non-jurisdictional mechanisms that are intended to prevent, manage, resolve or settle disputes. Thus, the expression alternative dispute resolution is, somewhat, technically insufficient to account for the whole range of options (or alternatives) available. This article re-examines the notion of ADR and provides a novel insight into the past, present and future of this relatively new discipline.
Keywords: ADR; alternative dispute resolution; access to justice